PROSPEK PENGEMBANGAN USAHA IKAN SALAI PATIN DESA KOTO MASJID KECAMATAN XIII KOTO KAMPAR KABUPATEN KAMPAR - Arizal '; Syakdanur Nas; Hardisem Syabrus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Fish Salai is a kind of traditional food at affordable prices and has a distinctive taste and savory. Demand for fish Salai in the village of Koto Masjid enormous because catfish smoked fish processing centers exist only in the village of Koto Masjid and also Salai Fish Marketing area is generally prevalent in the area Riau Province and outside the area of Riau Province. The purpose of this study was to determine Prospects Ikan Patin Salai seen from Aspects of Revenue and Business Development in the future. Respondents were interviewed are entrepreneurs Salai fish processors in the village of Koto Masjid District XIII Koto Kampar with numbered sample of 7 respondents. The results showed an overall revenue smoked fish processing, on average, net income of Rp. 19,026,201 and the number of comparison analysis to the average level of the ratio of R / C is 1.15. And the breakdown of a SWOT analysis business development aspects: 1). Maintaining taste delicious, distinctive and durable. 2). Maintain and increase the price and the production process is easy and fast. 3). Adding new marketing branch. 4). Producing its own raw materials in the form of catfish 5). Adding a variety of new products to prevent kebosananan smoked fish, catfish. 6). To collaborate with the owners of capital such as banks, cooperatives 7). And improve the quality of product variants. 8). Creating a good business management so as to increase the maximum benefit and coordinated effort 9). Promotion to Increase Market share is still open.Keywords: Prospects Development, SWOT Analysis, Business Salai catfish